Wayfinding for Pedestrians: Overview of the Role of Sidewalk Design - Lesmana, Widi; Hidayah, Retna; Bruri Triyono, Mochamad; Dahar Minghat, Asnul; Salina Mustakim, Siti (International Journal of Engineering and Technology, 2018)
The primary aim of this study was to describe the pattern of pedestrian movement and the main cause of studentsâ€™ selection in choosing those particular route. A qualitative research method was utilized for the purpose of data collection via an interview data retrieval technique. Findings were transcribed, coded, and analyzed manually. Findings indicated that studentsâ€™ difficulties in finding Rectorate Building were 27.5%. There were 75% of students who receive information for directions from the results of questioning with other students in the campus, while those who only read the guide map were only 25%. There were 55% of students choose route based on the closest distance, while comfort factor is 11.25%. Only 71.25% students use sidewalks, while those who do not always use pavements were 28.75%. Viewed from gender, it was indicated that difficulties in finding Rectorate Building was 44.7% from male and 38.1% from female. 60.5% of male and 73.8% of female prefer to ask verbally to find travel information, while 39.5% of male and 26.2% of female would read the guide map. 59.5% female and 31.5% of male prefer the shortest route. The users of sidewalks were 52.6% male and 69.2% female. This study contributes to the implementation and integration of sustainable green campus in Indonesia.Â Â